A model on factors affecting nurses adoption of health information technology - Binobaid, Saleh Abdullah (Cranfield University, 2017)
Healthcare organisations are using Health Information Technology (HIT) to improve efficiency, reduce cost and reduce medical errors. This study focused on the factors that influence the acceptance of HIT among nurses in Saudi hospitals. This research used a 6 stage mixed-methods research approach. Literature was used to search for established models and frameworks of technology acceptance, and the many factors that could play a role. In the field study, the nature of practical HIT issues at the Prince Sultan Military Medical City (PSMMC) and the Heraa Hospital were studied, and combined with literature to create a HIT Implementation Issues Framework. The framework consolidates elements from the Technological, Organisational, Environmental and Human dimensions. The researcher participated in further PSMMC projects in the design and implementation of the new Cardio Pulmonary Resuscitation System and the Nurses and Pharmacists’ Communication System. From the implementation experience, pertinent factors were added to the Technology Acceptance Model and the “Nurses Acceptance Model” was proposed. The proposed model has eleven independent parameters, two dependent parameters, as well as seven moderators of key relationships. A questionnaire with 71 entries was distributed to over 2800 nurses in 52 wards in PSMMC. SPSS was used for data screening and descriptive statistics. The SmartPLS software was used for analysis and testing of the proposed hypotheses. The findings refined the “Nurses Acceptance Model” and highlight the significance of User Involvement and Training. The “Nurses Acceptance Model” enhances the scientific understanding of variables that affect technology acceptance among nurses in Saudi hospitals. The HIT Implementation Issues Framework helps hospital decision makers to plan HIT projects to improve the likelihood of successful adoption.
Keywords: TAM3 model; TOE framework; nurses; critical factor; barriers; communication; CPR; CDSS; CPOE; Saudi Arabia